One Single Site Clinical Study: To Evaluate the Safety and Efficacy of Immunotherapy With Autologous Dendritic Cells, Cytokine-Induced Killer Cells in Primary Hepatocellular Carcinoma Patients - Xu, Kaiyue; Meng, Zhengjie; Mu, Xiaoxin; Sun, Beicheng; Chai, Yi (Frontiers in Oncology, 2020)
Dendritic cells (DCs) and cytokine-induced killer (CIK) cells play an important role in the anti-tumor immune response. In this study, we evaluated the clinical effectiveness of DC/CIK-CD24 immunotherapies to primary hepatocellular carcinoma patients who received radical resection. 36 resected primary hepatocellular carcinoma (HCC) patients were enrolled from August 2014 to December 2015. All patients received two or four times of DC/CIK immunotherapy after radical resection. 1–4 years patients’ survival rates were evaluated during the follow-up. The 4-year survival rate of patients who received two times of immunotherapy was 47.1%, and the rate of those who received four times of immunotherapies was 52.6%. Compared to baseline, after receiving the DC/CIK-CD24 autotransfusion, the serum Treg concentration of the patients decreased, while CD3+, CD4+, CD56+ increased slightly. The adverse effect of immunotherapy was I–II° transient fever and could be tolerable. DC/CIK-CD24 immunotherapy can delay the relapse time.